Produktivitas Alat Bongkar Muat (Crane) Terhadap Berthing Time - Danang Darunanto; Rr. Endang Wahyuni; Deslida Saidah (Institut Transportasi dan Logistik Trisakti, 2020)
PT. Indonesia Port Company (IPC) Tanjung Priok Container Terminal (TPK) is a company serving loading and unloading services of goods to and from ships. It is located at Ocean Going Pier which is a terminal with the main activity to serve loading and unloading container. The purpose of this study is to determine the correlation of productivity of Loading and Unloading Equipment (Crane) toward Berthing Time at the Ocean Going Pier at PT. Tanjung Priok TPC IPC Year 2016-2018. This research used quantitative methods with primary and secondary data sources. The expected output with the correlation of productivity of Loading and Unloading Equipment (Crane) toward Berthing Time at Ocean Going Pier at PT. Tanjung Priok TPC IPC Year 2016-2018 is that the company could make decisions and policy. The results show that there is a partially significant positive correlation between Crane variables (X₁) and Berthing Time (Y), where t-count 4.839> t-table 2.03224 and significant 0.000 <0.05, then Hₒ is rejected and Ha is accepted. Judging from the correlation coefficient between Productivity Crane (X₁) and Berthing Time (Y), 0.639, it is indicated as a strong correlation because it is in the interval of 0,600-0,799.